A comparative study of neuroprotective effect of angiotensin converting enzyme inhibitors against scopolamine-induced memory impairments in rats - Talha Jawaid; Shah Jahan; Mehnaz Kamal (Wolters Kluwer Medknow Publications, 2015)
The comparative study of neuroprotective effect of angiotensin converting enzyme inhibitors against scopolamine-induced neuroinflammation in albino Wistar rats was studied. Male albino rats were administered with scopolamine to induce memory impairment. The standard nootropic agent, piracetam (200 mg/kg b.w., [i.p.]), perindopril (0.1 mg/kg b.w., [i.p.]), enalapril (0.1 mg/kg b.w., [i.p.]), and ramipril (0.1 mg/kg b.w., [i.p.]) were administered in different group of animals for 5 days. On 5 th day, scopolamine (1 mg/kg b.w., i.p.) was administered after 60 min of the last dose of test drug. Memory function was evaluated in Morris water maze (MWM) test and pole climbing test (PCT). Biochemical estimations like glutathione (GSH), malondialdehyde (MDA), and acetylcholinesterase activity in the brain were estimated after completion of behavior study. All three test groups shows improvement in learning and memory in comparison to control group. Perindopril treated group showed a more effective significant decrease in escape latency time and transfer latency time compared to enalapril and ramipril treated group on day 4 in MWM test and PCT, respectively. Perindopril shows a significant reduction in MDA level and acetylcholinesterase activity and a significant rise in GSH level compared to enalapril and ramipril. The finding of this study indicates that Perindopril is more effective in memory retention compared to enalapril and ramipril.